Efforts to Control Work Accident Risks in Steel Construction Work Using the Job Safety Analysis (JSA) Method. (Case Study at PT. Xyz) - Muhammad Abdan Syakuro Billah; Akhmad Wasiur Rizqi; Moh. Jufriyanto (SITEKIN: Jurnal Sains, Teknologi dan Industri, 2023)
PT. XYZ is a PT engaged in general contracting, outsourcing, trading and services. In the company there are several workers who had work accidents. According to existing data for 2021-2022 in fabrication work, most accidents are related to negligence of workers at PT. XYZ, namely in the grinding process from being cut to tripping over cables, so the authors conducted this research aiming to reduce and minimize work accidents of workers in the workplace. This research was conducted by measuring accidents in every activity at PT. XYZ. Data processing is done by calculating the level of risk assessment, then determining the level of efficiency to be achieved using the Job Safety Analysis (JSA) method. The results of the risk assessment for each job show that there is one highest level of risk, namely in the drilling section with a likelihood value of three and a severity level of four. From the results of risk control in the fabrication process, it can be carried out by means of technical control (repairing or adding technical equipment such as installation Occupational Health and Safety signs), administrative control (briefing before work, using special tools to lift materials), and using PPE. Proposed improvements that can be given are the addition of several personal protective equipment suitable for work at the fabrication site, namely the use of gloves, wearing masks, gloves, safety shoes and welding goggles. From the results of risk control in the fabrication process, it can be carried out by means of technical control (repairing or adding technical equipment such as installing K3 signs), administrative control (briefing before work, using special tools to lift material), and using PPE. Proposed improvements that can be given are the addition of several personal protective equipment suitable for work at the fabrication site, namely the use of gloves, wearing masks, Occupational Health, and Safety signs), administrative control (briefing before work, using special tools to lift materials), and using PPE. Proposed improvements that can be given are the addition of several personal protective equipment suitable for work at the fabrication site, namely the use of gloves, wearing masks, gloves, safety shoes and welding goggles.